2022
DOI: 10.1038/s41467-022-30125-w
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted antibacterial action of Garcinia nanoparticles on Gram-negative bacteria

Abstract: Owing to the existence of the outer membrane barrier, most antibacterial agents cannot penetrate Gram-negative bacteria and are ineffective. Here, we report a general method for narrow-spectrum antibacterial Garcinia nanoparticles that can only be effective to kill Gram-positive bacteria, to effectively eliminate Gram-negative bacteria by creating transient nanopores in bacterial outer membrane to induce drug entry under microwaves assistance. In vitro, under 15 min of microwaves irradiation, the antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…The results demonstrated that LUT inhibited the growth of E. coli and S. aureus . Notably, the antimicrobial activity of LUT was higher against S. aureus than that of E. coli , indicating that the differences in cell wall structures between Gram-positive and Gram-negative microorganisms could affect the antibacterial effects of this compound [ 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that LUT inhibited the growth of E. coli and S. aureus . Notably, the antimicrobial activity of LUT was higher against S. aureus than that of E. coli , indicating that the differences in cell wall structures between Gram-positive and Gram-negative microorganisms could affect the antibacterial effects of this compound [ 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…External stimuli that can activate antimicrobial actions include light, magnets, microwaves, ultrasound, etc . Different metal-bearing nanomaterials possess distinct responses to these external stimuli. For example, semiconductor nanomaterials ( e.g.…”
Section: Metal-bearing Building Blocks With Stimuli-activable Antibac...mentioning
confidence: 99%
“…As mentioned above, SAMNs are a series of nanomaterials that remain dormant in the absence of external stimuli and selectively turn on when subjected to external stimuli, including light, magnetism, microwave, ultrasound, etc . The light triggered actions can be further divided into photodynamic and photothermal antibacterial therapies. The magnet triggered actions include magnetothermal and magnetophysical antibacterial modes.…”
Section: External Stimuli-activated On-demand Antibacterial Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies have reported tea nanoclusters as β-lactamase inhibitors for the treatment of multidrug-resistant bacterial pneumonia, 29 as well as the use of tea nanodots containing eight tea catechins with an average size of about 3 nm to kill MRSA and treat MRSA-H1N1 pneumonia. 30 In addition, Garcinia nanoparticles can effectively kill Gram-negative bacteria under microwave-assisted action, 31 and there is also MoS 2 /FeS polarization with Rhein interface to enhance microwave-catalyzed treatment of bacterial infections of osteomyelitis. 32 Similarly, under the synergistic excitation of near-infrared light and ultrasound, CuS forms a tight interface with curcumin to achieve rapid broad-spectrum bactericidal action.…”
Section: Introductionmentioning
confidence: 99%